Duration of Protection After Vaccination Against Yellow Fever: A Systematic Review and Meta-Analysis. (20th July 2022) - Kling, Kerstin; Domingo, Cristina; Bogdan, Christian; Duffy, Steven; Harder, Thomas; Howick, Jeremy; Kleijnen, Jos; McDermott, Kevin; Wichmann, Ole; Wilder-Smith, Annelies; Wolff, Robert
Abstract: The duration of protection after a single dose of yellow fever vaccine is a matter of debate. To summarize the current knowledge, we performed a systematic literature review and meta-analysis. Studies on the duration of protection after 1 and ≥2 vaccine doses were reviewed. Data were stratified by time since vaccination. In our meta-analysis, we used random-effects models. We identified 36 studies from 20 countries, comprising more than 17 000 participants aged 6 months to 85 years. Among healthy adults and children, pooled seroprotection rates after single vaccination dose were close to 100% by 3 months and remained high in adults for 5 to 10 years. In children vaccinated before age 2 years, the seroprotection rate was 52% within 5 years after primary vaccination. For immunodeficient persons, data indicate relevant waning. The extent of waning of seroprotection after yellow fever vaccination depends on age and immune status at primary vaccination. Abstract : Systematic review and meta-analysis of existing studies indicates a relevant waning of seroprotection after a single dose of yellow fever vaccination of different groups including healthy adults, children when vaccinated before the age of 2 years and immunodeficient persons.